THE ABUNDANCE OF ORNAMENTAL CORALS AFTER MASS DIE OFF IN 1997 ON THE PADANG SHELF REEF SYSTEM, WEST SUMATERA, INDONESIA - Ofri Johan; Anjang B. Prasetio; Idil Ardi; Amran R. Syam; Norman J. Quinn (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
ABSTRACTThe Indonesian Ministry of Marine Affairs and Fisheries aims to establish export quota ornamental corals based on scientifically-founded data from the natural environment. The purpose of this study was to determine the abundance of ornamental coral after mass die off in 1997. Ornamental corals were classified into three groups based on the guideline of ornamental coral propagation for trading purposes. Classification categories are rapid (3-6 months), middle (8-12 months), and slow growth rate (>24 months), which relates to their harvesting time when transplanted for the trade purpose. The survey method used line intercept transects to get coral condition data and belt transect with 2 m width to get ornamental coral data. Both line and belt transect have 30 m length and with three replicates. The study showed number of colony and abundance of ornamental coral for fast growth rate group such as Acropora sp (1348 col & 7.49 col/m2), Galaxea sp, Hydnophora exesa, H. microconus, Pocillopora damicornis, Stylopora sp and Montipora sp with the highest abundant found on Acropora sp and Montipora sp (1348 col & 7.49 col/m2). Whereas the coral which from middle growth rate were Leptoseris sp, Pavona sp, Platygyra sp, Favia sp, Favites sp with the highest abundant found on Favia sp (101 col & 0.56 col/m2).  Coral species typically used for ornamental coral trade within the slow growth rate category such massive coral were not found on this survey. Due to the massive coral die-off in 1997 and the paucity of ornamental corals, the utilization of ornamental coral should be supported by coral transplantation and the broodstock of slow growth of coral taken from other area.  Keywords: ornamental coral, abundant, mass die off, Padang Waters